Pengaruh Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Moderasi - Ayu Minarma Pasaribu; Eli Safrida; Jojor Lisbet Sibarani; Anita Putri (Politeknik Ganesha Medan, 2025)
The volatility of firm value in Indonesia’s consumer non-cyclicals sector in recent years reflects investors’ uncertainty regarding the effectiveness of corporate financial management. Despite the sector’s defensive nature, several leading firms have experienced a decline in stock performance, raising concerns about the role of internal financial factors in determining firm value. This study aims to examine the effect of capital structure and financial performance on firm value, with firm size as a moderating variable. The study employs a quantitative approach using secondary data from the annual reports of 40 consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the 2020–2024 period, resulting in 200 observations. Data were analyzed using Moderated Regression Analysis (MRA) with SPSS version 27. The results show that capital structure (DER) and financial performance (ROA) have a positive effect on firm value. Moreover, firm size strengthens the relationship between financial performance and firm value but fails to moderate the effect of capital structure on firm value. This study fills the gap by providing evidence from the post-pandemic period, focusing on a defensive sector where firm size may no longer signal financial strength effectively. The findings contribute to both theory and practice by emphasizing that managers in the consumer non-cyclicals sector should maintain optimal leverage and profitability to sustain investor confidence and firm value stability.